2012
DOI: 10.1111/j.1749-6632.2012.06543.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial magnetic stimulation on the modulation of gamma oscillations in schizophrenia

Abstract: Cognitive dysfunction is suggested to be the best predictor of functional outcome in schizophrenia. Therefore, new diagnostic and treatment strategies are needed to both ascertain the biological underpinning of cognitive deficits and to restore them. Modulation of gamma oscillations (30-50 Hz) has been associated with cognitive performance, particularly in the dorsolateral prefrontal cortex (DLPFC). In this manuscript, we review evidence for gamma modulation deficits during cognitive performance in schizophren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 79 publications
(182 reference statements)
1
37
0
Order By: Relevance
“…Cortical excitability has been extensively investigated in the primary motor-cortex (M1) using transcranial magnetic stimulation (TMS) and electromyography recordings (Rogasch et al 2014a), but recent studies opened the window for the assessment of the frontal lobe by combining TMS with electroencephalography (EEG) (Farzan et al 2012;Rogasch et al 2014b). As detailed in one meta-analysis (including 12 studies) and in one systematic review (including 24 studies), reduced TMS-induced intracortical inhibition in M1 has been consistently shown in schizophrenia patients Radhu et al 2013).…”
Section: Cortical Excitabilitymentioning
confidence: 99%
“…Cortical excitability has been extensively investigated in the primary motor-cortex (M1) using transcranial magnetic stimulation (TMS) and electromyography recordings (Rogasch et al 2014a), but recent studies opened the window for the assessment of the frontal lobe by combining TMS with electroencephalography (EEG) (Farzan et al 2012;Rogasch et al 2014b). As detailed in one meta-analysis (including 12 studies) and in one systematic review (including 24 studies), reduced TMS-induced intracortical inhibition in M1 has been consistently shown in schizophrenia patients Radhu et al 2013).…”
Section: Cortical Excitabilitymentioning
confidence: 99%
“…Second, brain stimulation via repetitive transcranial magnetic stimulation (rTMS) has been employed to rescue cognitive impairment [90]. Such studies have shown that rTMS can be employed to modulate GBO activity in the dorsolateral prefrontal cortex [91]. More recently, bilateral cortex rTMS was observed to improve performance in a visual n-back task (pre vs. post) in schizophrenia patients [92].…”
Section: Potential For Rescue Of Nmda Hypofunction-induced Cortical Cmentioning
confidence: 99%
“…It is also significant that the role attributed to θ in the present dynomic model gains support from the finding that this rhythm has greater amplitude in left superior temporal cortex during auditory hallucinations in schizophrenia (Ishii et al, 2000), as opposed to steady θ during resting state, with patients being seemingly incapable of regulating chunking operations. Given the identification of such dysrhythmias in schizophrenia, repetitive TMS (rTMS) could be used as a therapeutic intervention to modulate the oscillations responsible for the abnormal linguistic profile documented above, as has been done to improve performance on visual tasks (Farzan et al, 2012; Barr et al, 2013). The oscillopathic profile constructed here is presented in Table 1.…”
Section: From Brain Rhythmicity To Language Deficits In Schizophreniamentioning
confidence: 99%